2013
DOI: 10.4111/kju.2013.54.12.816
|View full text |Cite
|
Sign up to set email alerts
|

Priapism: Current Updates in Clinical Management

Abstract: Priapism is a persistent penile erection that continues for hours beyond, or is unrelated to, sexual stimulation. Priapism requires a prompt evaluation and usually requires an emergency management. There are two types of priapism: 1) ischemic (veno-occlusive or low-flow), which is found in 95% of cases, and 2) nonischemic (arterial or high-flow). Stuttering (intermittent or recurrent) priapism is a recurrent form of ischemic priapism. To initiate appropriate management, the physician must decide whether the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 37 publications
0
36
0
1
Order By: Relevance
“…It is often observed in males aged 20-50. 2,3 Although the possible causes of priapism differ according to priapism types, it is observed that it is mostly related to idiopathic and iatrogenic causes. Alcohol, medicine, drug use (21%), perineal trauma (12%), and or sickle cell nephropathy (5%) are other possible etiological causes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is often observed in males aged 20-50. 2,3 Although the possible causes of priapism differ according to priapism types, it is observed that it is mostly related to idiopathic and iatrogenic causes. Alcohol, medicine, drug use (21%), perineal trauma (12%), and or sickle cell nephropathy (5%) are other possible etiological causes.…”
Section: Introductionmentioning
confidence: 99%
“…Shuttering priapism is demonstrated by recurrent and intermittent erections. [1][2][3][4] Due to the frequent use of phospodiesterase enzyme 5 (PDE5) inhibitors in erectile dysfunction (ED) treatment and the use of penile Doppler ultrasonography (PDU) for ED diagnosis, priapism cases have increased recently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, abdominal and rectal examination should be done to exclude the presence of malignity which may cause ischemic priapism. 3,6 …”
Section: Physical Examinationmentioning
confidence: 99%
“…5,6 Priapism is an urgent urological disease which should be managed well since it may cause severe penile function disorder. Our aim in this article is presenting appropriate management of priapism in the light of current literature.…”
Section: Introductionmentioning
confidence: 99%